CYBER CRIME DAN POTENSI MUNCULNYA VIKTIMISASI PEREMPUAN DI ERA TEKNOLOGI INDUSTRI 4.0 - Neri Widya Ramailis (SISI LAIN REALITA, 2020)
The phenomenon of the industrial revolution 4.0 has had many influences, both positive and negative for society. It is undeniable that slowly everything has turned to digital. So that the interaction between humans and technology is inevitable. Such developments make digitization even more difficult to recognize, because everything is now integrated, everything now requires the internet. The opportunities for cyber criminals are getting wider, various kinds of cyber threats continue to emerge and this is a challenge for users. So many crimes that occur today in cyberspace or what is known as cyber crime, especially affect women. There are cases of illegal content (illegal content), violations of privacy (infringement of privacy), threats of private photo or video distribution (malicious distribution), online defamation, to online recruitment (online recruitment). The high number of online-based gender violence, especially for women, seems to open our eyes to always wisely use internet technology in carrying out activities and routines of daily life.